CROSS-CULTURAL PRAGMATIC ANALYSIS OF POLITENESS STRATEGIES USED BY THE AUSTRALIAN AND INDIAN CHARACTERS IN “LION” - Sulalah, Anis (Lire Journal (Journal of Linguistics and Literature), 2025)
This analysis investigated the representation of characters in the cinematic work “Lion.” Used various kinds of politeness strategies. This study aims to analyze the positive and negative politeness strategies used by characters from Australia and India, in addition to determine the factors that shape these strategies. This study applies a qualitative approach. As a result, the conversations in the movie are carefully transcribed and analyzed descriptively through the perspective of politeness theory (Brown, 2020) and s cross-cultural pragmatics (Wierzbicka, 2009) to identify the influence of the characters' cultural backgrounds on their strategic communication choices. The conversations that occur between the Australian and Indian characters in the film serve as a valuable repository of information, that includes both positive and negative politeness strategies. To obtain the data, the researcher uses a few processes, including watching the movie, taking notes, and choosing conversations in which the actors use both positive and negative politeness strategies frequently. The findings of this study reveal that a total of 121 sentences were classified as either negative or positive politeness, with 68 instances identified as negative politeness and 53 as positive politeness strategies. The application of both negative and positive politeness strategies articulated by the characters is primarily influenced by their cultural context.